GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 126 species occurrences available in GBIF matching the query: TaxonKey: Aves Geometry: POLYGON((-98.1 17.8,-98.1 17.5,-97.8 17.5,-97.8 17.8,-98.1 17.8)). The dataset includes 126 records from 2 constituent datasets: 114 records from EOD - eBird Observation Dataset. 12 records from iNaturalist Research-grade Observations. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences